Cachoeira do Sul: Vamos conhecer? Elaboração de material paradidático a partir do patrimônio histórico - Rodrigues, Antoniela A'Costa (2020)
This work proposes the elaboration of a didactic material about the Cachoeira do Sul county formation, bounded to teachers and students of basic education’s utilization. This proposal aims to fulfill the teachers’ request regarding specific pedagogical materials about the county’s history, since these materials don’t exist yet. We chose to use the Patrimonial Education methodology for creating this material for understanding that it allows the city culture’s valorization, once it was founded 200 years ago and have being occupied since before that. We also consider that this methodology makes school closer to public spaces, helping to develop skills and abilities needed to support citizenship exercise. In order to do so, this work brings a brief history of Cachoeira do Sul county, located in Rio Grande do Sul, Brazil, since the prime years of its occupation in the 18th century until the turn of the 19th to the 20th century. We emphasized the convergence of different human groups who constituted the local people during this period: native, Portuguese, enslaved Afro-descendants, Azorean, German and Italian — this way considering the multiculturalism inherent to the local development through the years. Beyond bringing a local history brief, there are also old and recent photographies, illustrations and other images. Pedagogical activities suggestions are included at the end of each chapter of the didactic material. A special chapter bounded to teachers brings other pedagogic proposals, besides including complementary references such as publications, videos, websites addresses and didactic games.